The training load of aerial skiing - Keaney, E.; Withers, S.; Parker-Simmons, S.; Gastin, P.; Netto, K. (International Journal of Performance Analysis in Sport, 2016)
This study quantified the training load experienced by elite aerial skiers. Nine elite female aerial skiers were monitored during 16 training sessions over a 13 day period. Time-motion, landing impact and heart rate (HR) data were measured from 688 jumps using integrated GPS, accelerometer and HR transmitters while rating of perceived exertion (RPE) was taken using Borg's scale. Each jump was delineated into five components from the GPS time-motion data to determine the work to rest ratios. Participants completed 16 ± 3 jumps per session with a work to rest ratio of 1.9:1 Heart rates averaged 65 ± 3.1% HRmax and peaked at 85 ± 4.4% HRmax while and an RPE score of 12 ± 1 was evoked. Landing impacts were significantly higher (p = 0.001) when participants jumped off ramps with a larger take-off angle or when they completed jumps with a mid-air rotation. The training load experienced by elite aerial skiers may be causative of the high incidence of injuries reported. Significantly differing levels of impact load during the study suggest training load for these athletes can be easily modified and periodised allowing optimised performance and minimised injury.